Holistic pedagogy for nurturing faithful, resilient and empathetic students - in UNTAG Semarang architectural education - Eko Nursanty; Loekman Muhamadi; Anwar Anwar (SARGA Jurnal Arsitektur UNTAG Semarang, 2019)
Nowadays education is often seen as a way to improve the "quality" of human life. Education is often considered as a benchmark for future material success and strength. Some study programs are perceived as the enabler of that hopes and become the dreams of many people. On the other hand, some study programs are considered "boring" and less desirable. This study aims to provide a different perspective that the educational process is fundamentally a continuous process and not a linear progression towards a utopian goal that many people expect. Human being possesses various physical, mental and intellectual potentials that can be nurtured through various innovative pedagogical methods. The research was conducted on some architecture students of UNTAG Semarang using qualitative methods of deductive case studies with comprehensive interview techniques. The analysis was carried out using the "Butterfly" method that scrutinized two seemingly opposing sides and found a balance between the opposites. The study results are the identification and formulations of several dominant elements that equally playing important roles in the architectural educational process, specifically focusing on the human’s spiritual, intellectual, and physical sides.  Those elements, supported by the environmental context, can produce various combinations of new values, knowledge, and skills, that are deeply rooted in the field of knowledge and in their daily lives.